Front Cover: Host–Guest Binding Hierarchy within Redox‐ and Luminescence‐Responsive Supramolecular Self‐Assembly Based on Chalcogenide Clusters and γ‐Cyclodextrin (Chem. Eur. J. 51/2018). Issue 51 (21st August 2018) - Ivanov, Anton A.; Falaise, Clément; Abramov, Pavel A.; Shestopalov, Michael A.; Kirakci, Kaplan; Lang, Kamil; Moussawi, Mhamad A.; Sokolov, Maxim N.; Naumov, Nikolay G.; Floquet, Sébastien; Landy, David; Haouas, Mohamed; et al.
Abstract : Rhenium‐containing octahedral clusters [Re6 Q8 (CN)6 ] 4− with Q=S, Se or Te exhibit high propensity to interact withγ ‐cyclodextrin in aqueous solutions, leading to host–guest supramolecular assemblies, driven by the chaotropic nature of these ions. Encapsulation processes give rise to significant alterations of the intrinsic physical–chemical properties of the cluster core, such as decreasing of the redox potential and luminescence enhancement. Such an approach appears relevant for developing advanced multifunctional materials useful for redox photocatalysis or biomedical applications. More information can be found in the Full Paper by P. A. Abramov, M. Haouas, E. Cadot et al. onpage 13467 .